2006
DOI: 10.1371/journal.pone.0000023
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Tumor-Selective Approach to Treat Metastatic Cancer

Abstract: BackgroundPatients diagnosed with metastatic cancer have almost uniformly poor prognoses. The treatments available for patients with disseminated disease are usually not curative and have side effects that limit the therapy that can be given. A treatment that is selectively toxic to tumors would maximize the beneficial effects of therapy and minimize side effects, potentially enabling effective treatment to be administered.Methods and FindingsWe postulated that the tumor-tropic property of stem cells or progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
144
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(149 citation statements)
references
References 39 publications
5
144
0
Order By: Relevance
“…13,14 These studies demonstrated that 90% of mice bearing multiple neuroblastoma metastases were disease-free, following treatment with neural progenitor cells expressing rCE and CPT-11 administration. In addition, no increase in toxicity was observed in these animals and doses of CPT-11 were used that are tolerable in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 These studies demonstrated that 90% of mice bearing multiple neuroblastoma metastases were disease-free, following treatment with neural progenitor cells expressing rCE and CPT-11 administration. In addition, no increase in toxicity was observed in these animals and doses of CPT-11 were used that are tolerable in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since the activation of CPT-11 by humans is relatively inefficient, we have proposed and developed an enzyme/prodrug therapy approach, using a rabbit liver CE (rCE), that can proficiently activate the drug. [8][9][10][11][12][13][14] Consequently, expression of rCE in human tumor cells, grown either in culture or as xenografts in immune-deprived mice, results in increased sensitivity to CPT-11. 8,12 However, the application of rCE to an enzyme/prodrug therapy approach in humans may be limited due to the potential immunogenicity of the lagomorph protein.…”
Section: Introductionmentioning
confidence: 99%
“…CM-DiI is a fluorescent dye suitable for tracking cells in vivo because it is non-diffusible and persists for at least 10 weeks by strongly binding to cellular thiols via a covalent bond. 27 Fluorescence staining analysis…”
Section: Mice Xenograft Model Derived From Mda-mb-231 Cellsmentioning
confidence: 99%
“…[7][8][9] In addition, NSCs can target brain metastasis in leptomeningeal medulloblastoma, breast cancer, melanoma and disseminated neuroblastoma. 8,[10][11][12] Therefore, we adopted NSCs as a targeting delivery system for subdural medulloblastomas, which serves as a disseminated tumor model. Gene-directed enzyme prodrug therapy has been one of the therapeutic strategies in stem cell-based gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…15 The activation level of CPT-11 in human plasma is very low because of the lack of CE activity in human blood. 16 As a result, a rabbit liver CE (rCE) that is 100-fold more efficient than human CE 10,12,[17][18][19] can be used for enzyme and prodrug therapy in combination with CPT-11 to improve therapeutic efficacy. 17,19 In the present study, we administered rCE expressing NSCs intravenously (i.v.)…”
Section: Introductionmentioning
confidence: 99%